Cover Image. (10th January 2023) - Pandey, Nitesh; Andres, Christian; Kumar, Satish
Abstract : The cover image is based on the Review Article Mapping the corporate governance scholarship: Current state and future directions by Nitesh Pandey et al., https://doi.org/10.1111/corg.12444 .